The efficacy and safety of acupuncture in nonalcoholic fatty liver disease: A systematic review and meta-analysis of randomized controlled trials. Issue 38 (24th September 2021) - Chen, Peiwen; Zhong, Xin; Dai, Yunkai; Tan, Meiao; Zhang, Gaochuan; Ke, Xuehong; Huang, Keer; Zhou, Zunming
Abstract: Background: The aim of this study was to determine the efficacy and safety of acupuncture treatment (AT) or acupuncture plus conventional medicine (CM) versus CM alone using a meta-analysis of all published randomized controlled trials (RCTs) for nonalcoholic fatty liver disease (NAFLD). Methods: Eight databases were searched independently from inception to April 30, 2020. RCTs were included if they contained reports on the use acupuncture or the use of acupuncture combined with CM and compared with the use of CM. Summary odds ratio (OR) and 95% confidence intervals (CIs) were used to calculate the overall clinical efficacy. Secondary outcomes, namely aspartate aminotransferase, alanine aminotransferase, total cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and body mass index, were calculated by mean difference with 95% CIs. Results: After the final screening, 8 RCTs with 939 patients were included. This meta-analysis showed that AT was superior to CM in improving overall clinical efficacy (OR = 3.19, 95% CI: 2.06–4.92, P   <  .00001). In addition, AT plus CM could significantly improve overall clinical efficacy compared to treatment with CM alone (OR = 5.11, 95% CI: 2.43–10.75, P   <  .0001). Moreover, the benefits were also demonstrated in other outcomes, including alanine aminotransferase, aspartate aminotransferase, total cholesterol, triglyceride, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol indexes. However, AT plus CM could not decrease body mass index levels in comparison with CM. The safety profile of Acupuncture therapy was satisfactory. Taichong, Zusanli, Fenglong, and Sanyinjiao were major acupoints on NAFLD treatment. Conclusion: Acupuncture may be effective and safe for treatment of NAFLD. However, due to insufficient methodological quality and sample size, further high-quality studies are needed.